Cultural diversity: how to make it work? - Madibekova, Diana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In this paper the author analyzes the importance of cultural diversity in modern world. The aim of this article is to present the board issue of cultural diversity that is the subject of interest of various academic disciplines. The text is also a reflection on a question about the way in which contemporary national cultures change under the influence of global trends.
Keywords: cross cultural communication; culture; globalization; diversity; challenges